Recurrent head and neck cancer – salvage therapy options - Łukaszczyk-Wideł, Beata; Wideł, Maciej; Składowski, Krzysztof (Contemporary Oncology/Współczesna Onkologia, 2008)
Despite continuous progress in head and neck cancer treatment, local and/or nodal recurrence is the most frequent reason for oncological treatment failure. The aim of this article is to review literature data about salvage treatment options. It describes three fundamental methods of treatment – surgery, especially used in oral, pharyngeal and laryngeal cancer recurrence, retreatment with radiation therapy and palliative chemotherapy. The limitation of salvage therapy is high risk of complications, but using the new achievements of this method lowers the risk of complications and improves the therapeutic index. Reconstructive surgery with microanastomoses, modern techniques of radiotherapy such as IMRT or radiosurgery or targeted therapy seem to be a chance for selected patients with recurrent head and neck cancer.